EFECTIVITY OF UNIT WALL FINISHING WITH STICK ON WALL METHOD IN CATTLEYA TOWER SAKURA GARDEN CITY APARTMENT PROJECT, EAST JAKARTA - Muhammad Rafky; Maryo Inri Pratama; Ika Bali; B.M.A.S. Anaconda Bangkara (Universitas Tarumanagara, 2022)
In building construction, interior wall finishing work usually uses conventional methods, namely plastering and nat grout. At Cattleya Tower Sakura Garden City Apartment, East Jakarta, the unit wall finishing uses a more modern method: Stick on wall. The Stick on wall method uses alternative finishing materials other than plaster and nat grout as a hebel wall covering made of large boards covered with thick paper which must be glued with a glue-like material to the hebel walls. The use of this method in the apartment case aims to speed up the project construction process because 90% of the units in Cattleya Tower have been sold, so the completion of the project must be realized immediately. This study was conducted to evaluate the effectiveness in terms of cost and time of the Stick on wall finishing method compared to the plastering and nat grout method. By calculating using the SNI method and considering other aspects such as transportation from the supplier to the project site, it is known that wall finishing work using stick on wall is 0.74% cheaper than wall finishing work using plaster and nat grout. As for the comparison of work time, work using stick on wall is 74.58% faster than wall finishing work using plaster and nat grout with a difference in working time of 52 days. Keywords: Stick on wall; wall finishing; plastering cost; nat grout Abstrak Dalam konstruksi bangunan, pekerjaan finishing dinding interior biasanya menggunakan metode konvensional yaitu plesteran dan nat grout. Di Cattleya Tower Sakura Garden City Apartment, Jakarta Timur, finishing dinding unit menggunakan metode yang lebih modern: Stick on wall. Metode Stick on wall menggunakan bahan finishing alternatif selain plaster dan nat grout sebagai penutup dinding hebel yang terbuat dari papan besar yang dilapisi kertas tebal yang harus direkatkan dengan bahan sejenis lem pada dinding hebel. Penggunaan metode ini pada kasus apartemen tersebut bertujuan untuk mempercepat proses konstruksi proyek karena di Cattleya Tower tersebut unit yang telah terjual sebesar 90%, sehingga penyelesaian proyek tersebut harus segera direalisasikan. Studi ini dilakukan untuk mengevaluasi efektivitas dari segi biaya dan waktu dari metode pekerjaan finishing dinding Stick on wall dibandingkan dengan metode plesteran dan nat grout. Dengan menghitung menggunakan metode SNI dan mempertimbangkan aspek lain seperti transportasi dari pemasok ke lokasi proyek, diketahui bahwa pekerjaan finishing dinding menggunakan stick on wall lebih murah 0,74% dibandingkan pekerjaan finishing dinding menggunakan plesteran dan nat grout. Sedangkan untuk perbandingan waktu pengerjaan, pekerjaan menggunakan stick on wall lebih cepat 74,58% dibandingkan pekerjaan finishing dinding menggunakan plesteran dan nat grout dengan selisih waktu kerja adalah 52 hari.